Studies on mass transport properties of Alginate capsule - Zahidah Mohammad Yusoff (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
The alginate and chitosan were used for the preparation of controlled release solute. There are no systematically studies conducted to understand the correlation and the influence of process parameter on the mass transport properties of alginate capsule. The capsules were made by extrusion dripping method, dropping a solution of chitosan into calcium alginate solution. The spherical factor for alginate capsule (AC), <0.05 mm mean that the shape of capsule is spherical. The smaller needle diameter which 0.5 mm gives the small diameter of capsule, the mass transport rate of solute ingress and egress is slowly either the solute enter and release from the capsule. The evaluation of mass transport coefficient value (h) is proposed as a supplementary method for characterization of capsules with semi-permeable membrane. Low molecular mass transfer coefficient in order the small of capsule diameter with 0.5 mm needle diameter is 3.580.13 mm. Experimentally determined the mass transport properties for a selected needle diameter for continue different concentration of chitosan, molecular weight of alginate and different solute enable a ranking of encapsulation materials and standardization of measurements of transport properties.